Risk-Management in the Field of Vaccine Prevention as one of the Directions of Ensuring Epidemiological and Biological Safety - I. V. Feldblium (Эпидемиология и вакцинопрофилактика)
The article presents the basic positions of managing the vaccine prevention risks on the population level. The science-based necessity of transition from the assessment of the effectiveness of mass vaccinal prevention in terms of incidence rates to managing potential risks of vaccine prevention. The prospects for further development of this methodology were determined.